2011
DOI: 10.1016/j.ajhg.2011.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of POLR3A Encoding a Catalytic Subunit of RNA Polymerase Pol III Cause a Recessive Hypomyelinating Leukodystrophy

Abstract: Leukodystrophies are a heterogeneous group of inherited neurodegenerative disorders characterized by abnormal white matter visible by brain imaging. It is estimated that at least 30% to 40% of individuals remain without a precise diagnosis despite extensive investigations. We mapped tremor-ataxia with central hypomyelination (TACH) to 10q22.3-23.1 in French-Canadian families and sequenced candidate genes within this interval. Two missense and one insertion mutations in five individuals with TACH were uncovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
241
2
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(263 citation statements)
references
References 25 publications
9
241
2
8
Order By: Relevance
“…Accordingly, the specific expression of rpc9 in the CHT region may indicate that the rapidly expanding HSPCs require many more Pol III transcripts. In fact, in the absence of Pol III components, recent reports demonstrated neuron-specific dysfunction in humans (Bernard et al, 2011;Saitsu et al, 2011;Wong et al, 2011) and digestive organ-specific defects in zebrafish (Yee et al, 2007). Intriguingly, the rpc9 heterozygous mutant embryos have no hematopoietic defects and can develop into fertile adults, similar to rpl11 (encoding ribosome protein Rpl11), nop10 (18S RNA processing) and kri1l (18S RNA maturation) mutants in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the specific expression of rpc9 in the CHT region may indicate that the rapidly expanding HSPCs require many more Pol III transcripts. In fact, in the absence of Pol III components, recent reports demonstrated neuron-specific dysfunction in humans (Bernard et al, 2011;Saitsu et al, 2011;Wong et al, 2011) and digestive organ-specific defects in zebrafish (Yee et al, 2007). Intriguingly, the rpc9 heterozygous mutant embryos have no hematopoietic defects and can develop into fertile adults, similar to rpl11 (encoding ribosome protein Rpl11), nop10 (18S RNA processing) and kri1l (18S RNA maturation) mutants in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Lysates from all patients examined were strongly impaired in their ability to convert AT-rich DNA to immune-stimulatory RNA, whereas transcription of 5S rRNA was largely unaffected. Previous studies have identified mutations in POLR3A and POLR3B in patients with autosomal recessive 4H (hypomyelination, hypodontia, hypogonadotropic hypogonadism) leukodystrophy, which is a disease characterized by degeneration of the white matter in the brain (38)(39)(40). However, the functional impact of the POLR3 gene mutations in the 4H leukodystrophy patients on POL III activity remains to be established.…”
Section: Induction Of Ifns By At-rich Dna In Human Pbmcs Is Pol Iii-dmentioning
confidence: 99%
“…3 Several years later, tremor-ataxia with central hypomyelination (TACH) was described in French Canadian patients 4 and mapped to 10q22.3-10q23.31 with subsequent identification of the responsible gene, POLR3A, coding for the largest subunit of RNA polymerase III. 5 Mutations in POLR3A and POLR3B, encoding another subunit of this polymerase, were then shown to also cause 4H, as well as 2 other entities: "hypomyelination with cerebellar atrophy and hypoplasia of the corpus callosum," and "leukodystrophy with oligodontia." [6][7][8] The name Pol IIIrelated leukodystrophies has been suggested in order to include all the variations described above.…”
mentioning
confidence: 99%